Analysis of Government Regulations in Lieu of Law No. 1 of 2020: As a Response to the Urgency of the COVID-19 Pandemic - Putri, Aulia Kartika; Adli, Hinza Praitma; Habibullah, Akhmad (Department of Government Studies, Universitas Muhammadiyah Buton., 2023)
This study delves into the analysis of Government Regulations in Lieu of Law (PERPU) enacted by the president as a response to the urgency of the COVID-19 pandemic. It specifically focuses on PERPU No. 1 of 2020, which was issued during a state of coercive crunch without replacing or amending an existing or forthcoming law. The study employs a normative juridical or normative law research method using a statute and conceptual approach to examine the compliance of PERPU No. 1 of 2020 with the parameters outlined by the Constitutional Court. The findings reveal that the determination of the reason for the Health emergency in this PERPU seems subjective and is not in line with the parameters outlined by the Constitutional Court. The study concludes that the issuance of PERPU must be regulated more strictly and transparently to ensure that it is only utilized in exceptional situations, in accordance with the Constitution and its application is objective.